2018
DOI: 10.1016/j.celrep.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Characterization of the Hippo Signaling Pathway in Cancer

Abstract: SUMMARY Hippo signaling has been recognized as a key tumor suppressor pathway. Here, we perform a comprehensive molecular characterization of 19 Hippo core genes in 9,125 tumor samples across 33 cancer types using multidimensional “omic” data from The Cancer Genome Atlas. We identify somatic drivers among Hippo genes and the related microRNA (miRNA) regulators, and using functional genomic approaches, we experimentally characterize YAP and TAZ mutation effects and miR-590 and miR-200a regulation for TAZ. Hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
291
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 358 publications
(357 citation statements)
references
References 54 publications
18
291
1
3
Order By: Relevance
“…Accumulating evidences suggest that dysregulation of the Hippo pathway and hyperactivation of YAP have been frequently associated with various types of human cancers including breast, liver, lung, ovary, colon, kidney, brain and others 8,9,54 . Moreover, recent human cancer genome studies also connected the genetic alteration of the Hippo pathway components with cancer development 55,56 . Given the evolutionarily conserved roles for the Hippo pathway components, it will be interesting to characterize the oncogenic alteration of the Hippo pathway in evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidences suggest that dysregulation of the Hippo pathway and hyperactivation of YAP have been frequently associated with various types of human cancers including breast, liver, lung, ovary, colon, kidney, brain and others 8,9,54 . Moreover, recent human cancer genome studies also connected the genetic alteration of the Hippo pathway components with cancer development 55,56 . Given the evolutionarily conserved roles for the Hippo pathway components, it will be interesting to characterize the oncogenic alteration of the Hippo pathway in evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear translocation of YAP1 is regulated by multiple mechanical stimuli, such as matrix stiffness, epithelial stretching and cell density [2][3][4][25][26] . To test the effects of mechanical environment on YAP1 localization, we removed utricles from P15 mice and placed them in Such data suggest that placement in culture leads to temporary YAP1 nuclear translocation, but that nuclear immunoreactivity of YAP1 returned to normal (0 hr time point) levels by 24 hr in vitro ( Fig.…”
Section: Placement In Organotypic Culture Evokes Transient Nuclear Trmentioning
confidence: 99%
“…The Hippo/YAP1 pathway is an evolutionarily conserved signaling network known to be involved in regulating tissue size and cell number during development [2][3][4][25][26] , The transcriptional coactivator YAP1 is the primary effector of Hippo signaling. Under normal conditions, YAP1 is sequestered in the cytoplasm and targeted for degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing only on tumours that have lost merlin function would probably miss meso theliomas in which Hippo signalling is inhibited by inactivation of other proteins, such as LATS1 and LATS2. A previous study 17 of the Hippo pathway in various cancers has revealed that 22 genes are commonly trans cribed by YAP and TAZ, and this transcriptional profile might offer a way to identify ferroptosis-sensitive tumours. Further more, because this profile was found 17 in several types of tumour, triggering ferroptosis might be worth exploring for cancers other than mesothelioma.…”
mentioning
confidence: 98%